Human rights and environmental sustainability - Woods, Kerri; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub., 2010)
Human Rights and Environmental Sustainability challenges the assumed harmony between human rights norms and the demands of environmental sustainability, by addressing conceptual, normative, and political questions surrounding the interaction between the two.
ch. 1. Globalization, human rights and the environment -- ch. 2. Human rights : moral authority and philosophical doubts -- ch. 3. The contemporary human rights regime : some criticisms and an alternative -- ch. 4. Environmental sustainability and environmental values -- ch. 5. The institutions of sustainability : citizenship, democracy and justice -- ch. 6. Rights or sustainability ; rights and sustainability?
Includes bibliographical references and index.
Keywords: Human rights -- Environmental aspects; Sustainability -- Social aspects; Electronic books